Neutralizing the threat: harnessing broadly neutralizing antibodies against HIV-1 for treatment and prevention - Juan C Becerra; Lauren Hitchcock; Khoa Vu; Johannes S Gach (Microbial Cell)
Broadly neutralizing antibodies (bnAbs) targeting the human immunodeficiency virus-1 (HIV-1) have played a crucial role in elucidating and characterizing neutralization-sensitive sites on the HIV-1 envelope spike and in informing vaccine development. Continual advancements in identifying more potent bnAbs, along with their capacity to trigger antibody-mediated effector functions, coupled with modifications to extend their half-life, position them as promising candidates for both HIV-1 treatment and prevention. While current pharmacological interventions have made significant progress in managing HIV-1 infection and enhancing quality of life, no definitive cure or vaccines have been developed thus far. Standard treatments involve daily oral anti-retroviral therapy, which, despite its efficacy, can lead to notable long-term side effects. Recent clinical trial data have demonstrated encouraging therapeutic and preventive potential for bnAb therapies in both HIV-1-infected individuals and those without the infection. This review provides an overview of the advancements in HIV-1-specific bnAbs and discusses the insights gathered from recent clinical trials regarding their application in treating and preventing HIV-1 infection.